Analisis Vegetasi Herba Di Bukit Batu Putih dan Gunung Bulusaraung Dusun Bulu-Bulu Desa Tompobulu Resort Balocci Taman Nasional Bantimurung Bulusaraung Kabupaten Pangkep - Sari, Puspa; Wiharto, Muhammad; Hamka L, Hamka L (bionature, 2017)
Abstract. Descriptive research with survey method was performed to determine Importance Value Index (IVI), Richeness (S), Eveness Index (E), Diversity Index (H’), and Similarity Index (IS) of herb vegetation on White rock and Bulusaraung Mountain Bulu-bulu Countryside Balocci Resort Bantimurung Bulusaraung National Park. Sampling were performed in two directions they are White rock and Bulusaraung Mountain. Transect placed with random. In each transect, 10 plots were made with 2 m x 2 m, placed criss-cross with alternating intervals with 8 m range between each plot. Each herb was counted and identified to species level. IVI of each herb were obtained from relative density, relative frequency and relative dominance. Results showed that 33 speciment, 5 identified by genus level and 28 identified by species level. Species with highest IVI in White rock were O. hirtellus, G. repens, A. compressus, C. prostrate dan C. cordifolium while the lowest were C. gigantea, N. hirsututa, C. sicyoides, P. mollissimum dan A. longiloba. Species of Bulusaraung Mountain with highest IVI were P. bettle, A. longiloba, A. unilaterale, C. rotundatus dan P. mollissimum whereas the least were Macrothelypteris sp., H. peduncularis, Aglaonema sp., Hedychium sp., dan Habenaria sp. BBPH net worth at 23 while the value of species richness in G. Bulsar by 25 species; equity indices in both areas classified as moderate; and high species diversity index at The Mount Bulusaraung otherwise being in the area BBPH. Value IS in the area of Bukit Batu Putih and Mount Bulusaraung relatively low.Keywords: importance value index, richeness, eveness index, diversity index, similarity index, bantimurung bulusaraung national park, herbs vegetation.